2020
DOI: 10.1055/s-0040-1721312
|View full text |Cite
|
Sign up to set email alerts
|

The Response of the Tongue Epithelial on Cigarette Smoke Exposure as a Risk Factor for Oral Cancer Development

Abstract: Objective The aim of this study is to analyze the tongue epithelial response to cigarette smoke exposure on a number of macrophages, lymphocytes, plasma cells, and matrix metalloproteinase 9 (MMP-9) expression to determine the risk factor of oral cancer development. Materials and Methods Thirty Rattus norvegicus will be exposed to two kinds of cigarette smoke by a smoking pump for 4 and 8 weeks. The tongues were collected to analyze the number of macrophages, lymphocytes, and plasma cells with hematoxylin-eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…This results in genetic differences that are influential in cell division such as p53 so that susceptibility to genetic mutations is different between individual rats. 35 A previous study conducted by Prasetyaningtyas et al 17 and Ayuningtyas et al 36 showed that cigarette smoke exposure can increase the dysplasia degree and induce the risk of oral cancer development due to increased number of macrophages, lymphocytes, and MMP-9 expressions in the tongue epithelium.…”
Section: Discussionmentioning
confidence: 98%
“…This results in genetic differences that are influential in cell division such as p53 so that susceptibility to genetic mutations is different between individual rats. 35 A previous study conducted by Prasetyaningtyas et al 17 and Ayuningtyas et al 36 showed that cigarette smoke exposure can increase the dysplasia degree and induce the risk of oral cancer development due to increased number of macrophages, lymphocytes, and MMP-9 expressions in the tongue epithelium.…”
Section: Discussionmentioning
confidence: 98%
“…However, smoking and chronic irritation caused by ill-fitting dentures, as well as swallowing and inhaling environmental carcinogens at elevated internal body temperature, have been proposed to play a role in the development of malignant lesions. 3,9 Clinically, oral melanoma demonstrates as a slow-growing, asymptomatic, brown, purple, or black pigmentation with irregular borders and may appear as a rapidly expanding mass with or without ulceration. 1,10 The clinical differential diagnosis should exclude oral melanoma from normal variations 11 and other benign, harmless black lesions such as melanotic macule, smoker's melanosis, amalgam and graphite tattoos, and pigmented nevus.…”
Section: Discussionmentioning
confidence: 99%
“…However, smoking and chronic irritation caused by ill-fitting dentures, as well as swallowing and inhaling environmental carcinogens at elevated internal body temperature, have been proposed to play a role in the development of malignant lesions. 3 9 …”
Section: Discussionmentioning
confidence: 99%
“…This was in accordance with previous studies. [23][24][25][26][27] Smoking induces oral cancer risk development [28] Cigarettes contains N-nitrosamines and nicotine which lead to DNA mutations. This mutation encourages tu-mor initiation and promotion.…”
Section: Discussionmentioning
confidence: 99%